Diversity of Gibberellin 2-oxidase genes in the barley genome offers opportunities for genetic improvement - Jingye Cheng; Yong Jia; Camilla Hill; Tianhua He; Ke Wang; Ganggang Guo; Sergey Shabala; Meixue Zhou; Yong Han; Chengdao Li (Journal of Advanced Research)
Introduction: Gibberellin (GA) is a vital phytohormone in regulating plant growth and development. During the “Green Revolution”, modification of GA-related genes created semi-dwarfing phenotype in cereal crops but adversely affected grain weight. Gibberellin 2-oxidases (GA2oxs) in barley act as key catabolic enzymes in deactivating GA, but their functions are still less known. Objectives: This study investigates the physiological function of two HvGA2ox genes in barley and identifies novel semi-dwarf alleles with minimum impacts on other agronomic traits. Methods: Virus-induced gene silencing and CRISPR/Cas9 technology were used to manipulate gene expression of HvGA2ox9 and HvGA2ox8a in barley and RNA-seq was conducted to compare the transcriptome between wild type and mutants. Also, field trials in multiple environments were performed to detect the functional haplotypes. Results: There were ten GA2oxs that distinctly expressed in shoot, tiller, inflorescence, grain, embryo and root. Knockdown of HvGA2ox9 did not affect plant height, while ga2ox8a mutants generated by CRISPR/Cas9 increased plant height and significantly altered seed width and weight due to the increased bioactive GA4 level. RNA-seq analysis revealed that genes involved in starch and sucrose metabolism were significantly decreased in the inflorescence of ga2ox8a mutants. Furthermore, haplotype analysis revealed one naturally occurring HvGA2ox8a haplotype was associated with decreased plant height, early flowering and wider and heavier seed. Conclusion: Our results demonstrate the potential of manipulating GA2ox genes to fine tune GA signalling and biofunctions in desired plant tissues and open a promising avenue for minimising the trade-off effects of Green Revolution semi-dwarfing genes on grain size and weight. The knowledge will promote the development of next generation barley cultivars with better adaptation to a changing climate.